2005
DOI: 10.1007/s00360-005-0051-x
|View full text |Cite
|
Sign up to set email alerts
|

Water relations of the burrowing sandhill frog, Arenophryne rotunda (Myobatrachidae)

Abstract: Arenophryne rotunda is a small (2-8 g) terrestrial frog that inhabits the coastal sand dunes of central Western Australia. While sand burrowing is a strategy employed by many frog species inhabiting Australia's semi-arid and arid zones, A. rotunda is unique among burrowing species because it lives independently of free water and can be found nocturnally active on the dune surface for relatively extended periods. Consequently, we examined the physiological factors that enable this unique frog to maintain water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 25 publications
2
8
0
1
Order By: Relevance
“…Hopper and Gioia (2004) argue that throughout these climatic fluctuations, the Shark Bay region suffered the most severe climate change due to the massive differences in rainfall experienced in these regions during glacial maxima and minima. A. rotunda is heavily reliant on soil moisture for dermal rehydration (Cartledge et al, 2006); limited rainfall may have diminished soil moisture which thereby restricted populations to coastal areas in the west, reinforcing fragmentation via uplift of the Victoria Plateau.…”
Section: Biogeography and Speciation In Arenophrynementioning
confidence: 99%
“…Hopper and Gioia (2004) argue that throughout these climatic fluctuations, the Shark Bay region suffered the most severe climate change due to the massive differences in rainfall experienced in these regions during glacial maxima and minima. A. rotunda is heavily reliant on soil moisture for dermal rehydration (Cartledge et al, 2006); limited rainfall may have diminished soil moisture which thereby restricted populations to coastal areas in the west, reinforcing fragmentation via uplift of the Victoria Plateau.…”
Section: Biogeography and Speciation In Arenophrynementioning
confidence: 99%
“…The few studies in controlled laboratory conditions exploring dryness effects on burrowing behaviour only investigate the occurrence of emergence (Hoffman and Katz, 1989;Jansen et al, 2001). Amphibians are able to rehydrate by absorbing water from surrounding soil (Booth, 2006;Ruibal et al, 1969), so it had been suggested that burrowing anurans exposed to dry conditions would dig deeper into the substrate to seek moisture and rehydrate (Cartledge et al, 2006b). However, this hypothesis remained unconfirmed.…”
Section: Introductionmentioning
confidence: 99%
“…Noncocooning Australian species mostly burrow in sandy soils, e.g. Heleioporus spp., Notaden nichollsi, Arenophryne rotunda, Myobatrachus gouldii (Bentley et al, 1958;Packer, 1963;Slater and Main, 1963;Tyler et al, 1980;Tyler et al, 2000;Paltridge and Nano, 2001;Thompson et al, 2005;Cartledge et al, 2006). As a burrowing medium, sand has the advantage for non-cocooning species of high water potential at relatively low moisture content, facilitating water absorption by a burrowed frog.…”
Section: Introductionmentioning
confidence: 99%
“…As a burrowing medium, sand has the advantage for non-cocooning species of high water potential at relatively low moisture content, facilitating water absorption by a burrowed frog. For example, the sandhill frog Arenophryne rotunda can maintain water balance in sand with a gravimetric water content of only 1-2% (Cartledge et al, 2006). Scaphiopus couchii burrow in soil consisting of a higher proportion of fine particles, which correspondingly requires higher moistures to generate water potentials favourable for water uptake by the frog (McClanahan, 1972).…”
Section: Introductionmentioning
confidence: 99%